DEVELOPMENT OF DIGITAL MARKETING ENTREPRENEURSHIP SORGHUM-BASED SUPPORTS NEW NORMAL - Endang Noerhartati; Pratiwi Dwi Karyati; Citrawati Jatiningrum; Nia Saurina; Lathifah Nur Karimah (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2021)
Sorghum-based food products as one of the alternative foods can be developed, but the problem is that these products have not been maximally marketed until now. Based on this, it is necessary to study and build marketing with a digital system to support the new normal. The purpose of this research is to develop digital marketing in sorghum-based agroindustry entrepreneurship. The research method used is qualitative research methods in entrepreneurship, descriptive qualitative action research type with data collection techniques observation and documentation, data were collected,  and SWOT analysis was carried out.  The results showed that sorghum products as a strength in the agroindustrial entrepreneurship process and alternative food diversification products support food security, strengthening the marketing sector to create and increase the potential of digital marketing; the weakness is that raw materials are not maximally available; the threat is competition for imported entrepreneurship products; the challenge is that sorghum products as an alternative food must become a national product. Conclusion: Creating a market for sorghum products as an alternative food is needed, and digital marketing as a solution to support the new normal.